Prevalence and Antimicrobial Susceptibility of Pathogens in Urinary Tract Infections - Mahmood, Maha A (Al-Nahrain Journal of Science, 2011)
الخلاصة: This study was done to assess the bacterial profile and antibiotic susceptibility pattern of urinary tract infections (UTIs) pathogens. For proper identification of causative microbial agents, mid stream urine samples from 459 patients with clinical symptoms suspected to be UTI were collected, cultured and subjected to appropriate biochemical tests. These samples were collected from Teaching Laboratories Center in Baghdad during the study period (1st January 2009 - 1st July 2009). The antimicrobial sensitivity test was carried out by disc diffusion technique using Muller- Hinton agar. 100 urine samples were cultured positive with a colony count equal or more than 105/ml while 359 cases were excluded as they were culture negative or exhibited mixed infections. Overall males to females ratio was 1:3.2. The most prevalence isolates were Escherichia coli with frequency rate of 50% followed by Enterobacter spp.(12%). Whereas, Klebsiella spp., Pseudomonas aeruginosa and Enterococcus faecalis showed frequency rate of 9% for each. Howevere, Proteus spp., Staphylococcus aureus, Staphylococcus epidermidis and Acinetobacter spp.showed frequency rate less than 5%. The majority of isolates were sensitive to imipenem (96%) followed by amikacin(89%) and nitrofurantion(69%) whereas, high level resistance was seen to cotrimoxazole, ampicillin and trimethoprim followed by cefoxitin, nalidixic acid, gentamicin and cefotaxime in decreasing order of frequency